SARS-CoV-2 neutralizing antibodies after first vaccination dose in breast cancer patients receiving CDK4/6 inhibitors. (December 2021) - Zagouri, Flora; Terpos, Evangelos; Fiste, Oraianthi; Liontos, Michalis; Briasoulis, Alexandros; Katsiana, Ioanna; Skafida, Efi; Markellos, Christos; Kunadis, Elena; Andrikopoulou, Angeliki; Kaparelou, Maria; Koutsoukos, Konstantinos; et al.
Abstract: Undoubtedly, the development of COVID-19 vaccines displays a critical step towards ending this devastating pandemic, considering their protective benefits in the general population. Yet, data regarding their efficacy and safety in cancer patients are limited. Herein we provide the initial analysis of immune responses after the first dose of vaccination in 21 breast cancer patients receiving cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors. The levels of neutralizing antibodies post vaccination were similar to the matched healthy controls, whereas no safety issues have been raised. Further exploration is needed to reduce the uncertainty of SARS-CoV-2 immunity among cancer patients under treatment. Highlights: Data on the efficacy and safety of COVID-19 vaccines in cancer patients are limited. 21 breast cancer patients under CDK4/6 inhibition enrolled to our prospective study. Nearly 30% of them developed favorable viral inhibition after the first dose. Immune responses did not differ between patient cohort and healthy controls.